Mask Use During COVID-19: A Social-Ecological Analysis. Issue 2 (March 2021) - Casola, Allison R.; Kunes, Brianna; Cunningham, Amy; Motley, Robert J.
To limit the spread of coronavirus disease 2019 (COVID-19), the Centers for Disease Control and Prevention issued recommendations that individuals wear face masks in public. Despite these recommendations, the individual decision to adhere and wear a mask may not be a simple decision. In this article, we examine the decision to wear a mask from a social-ecological perspective. Through critical analysis of societal, interpersonal and community, and intrapersonal influences, it is clear that the decision to wear a mask is multifaceted and influenced by constructs including public health recommendations and government mandates, racism and cultural norms, geography, household income, age, and personal attitudes. Understanding the multifactorial influences on mask wearing during COVID-19 is crucial for informing the creation and distribution of inclusive public health messaging regarding mask wearing now in the midst of an unprecedented health crisis, and in future unforeseen public health emergencies.